Nipple adenoma: A clinicopathological study over a period of six years in tertiary care center - H S Fathima Afshan; M Nirmal Daniel; A Santhosh Raj; Priyanka Singh; Elanthenral Sigamani (Indian Journal of Pathology and Microbiology)
Background: Nipple adenoma (NA) is a rare benign neoplasm of the nipple arising from the lactiferous duct. Often seen in middle aged women, presenting as a nodule, erosive, or ulcerative lesion and associated with serous or bloody discharge. Histologically, they comprise closely arranged tubules with papillary infoldings centered around the lactiferous ducts. It is most likely clinically confused with Paget’s disease and histologically with invasive breast carcinoma or its precursor lesions. The aid of immunohistochemistry is valuable in differentiating these entities and to definitively exclude malignancy. Materials and Methods: All cases with available slides and blocks, diagnosed as nipple adenoma, during the period of January 2015 to December 2021, will be identified through an appropriate query search from the pathology database. Clinico-radiological details and histopathology will be studied and analyzed. The available follow up data and clinical outcome will be assessed. Results: Sixteen cases of nipple adenoma were studied and the median age at diagnosis was found to be 37 years. Nipple discharge and swelling were the most common presentations. Ultrasound imaging was done in 14 cases with the median size of lesion being 0.8cms. Seven underwent excision biopsy followed by histopathological examination. The most common histological pattern observed is “adenosis” pattern. Immunostains p63, smooth muscle myosin heavy chain (SMMHC) and CK5/6 were performed. Nine cases were on follow up but none had recurrence. Conclusion: NA is a benign entity with varied histological patterns. Histopathological examination with the aid of immunohistochemistry helps in diagnosis and to rule out other mimickers. Surgical excision is the treatment of choice.